Stock market efficiency: a pooled mean group approach / Tay Bee Hoong ... [et al.] - Tay, Bee Hoong; Ramdhan, Nur 'Asyiqin; Hassan, Suzana; Kholib Jati, Muhamad Khodri; Mohamed Yousop, Nur Liyana (UiTM Cawangan Johor, 2019)
The efficient market theory has been widely focused on the market efficiency in the developed countries but not in the developing countries despite the valuable diversification opportunities developing stock markets offer. Therefore, the objective of this study is to examine the informational efficiency of stock markets in both the selected developed and developing countries. The informational efficiency is examined by the cointegration between stock return and its determinants, namely output, interest rate and exchange rate using the dynamics heterogeneous panel cointegration model over the period of 1994Q1 to 2016Q2. The results of the study reveal that there are long run relationships between stock return and the three observed economic indicators in the developed and developing countries. Evidenced by the information of real output and real interest rate that are impounded into the stock return, the study further revealed that stock markets in developed countries are semi strong form efficient. Therefore, one cannot use real output and real interest rate as trading rule to earn abnormal return in developed countries. On the other hand, the information on real output, real interest rate and real exchange rate have not fully captured by the stock return in the developing countries, thus demonstrate that these markets are informational inefficient. The overall findings suggest that output, interest rate and exchange rate can serve as important explanatory variables for the investors and policy makers in making investment and policy decisions by providing better understanding that the developed stock markets are relatively more informational efficient compared to developing stock markets.